Nonlinear age effects in tactile processing from early childhood to adulthood. Issue 7 (8th June 2022) - Kaur, Sakshi; Espenhahn, Svenja; Bell, Tiffany; Godfrey, Kate J.; Nwaroh, Chidera; Giuffre, Adrianna; Cole, Lauran; Beltrano, Winnica; Yan, Tingting; Stokoe, Mehak; Haynes, Logan; Hou, Tasha Yuntao; et al.
Abstract: Background: Tactile processing plays a pivotal role in the early stages of human development; however, little is known about tactile function in young children. An understanding of how tactile processing changes with age from early childhood to adulthood is fundamental in understanding altered tactile experiences in neurodevelopmental disorders, such as autism spectrum disorder. Methods: In this cross‐sectional study, 142 children and adults aged 3–23 years completed a vibrotactile testing battery consisting of 5 tasks, which rely on different cortical and cognitive mechanisms. The battery was designed to be suitable for testing in young children to investigate how tactile processing changes from early childhood to adulthood. Results: Our results suggest a pattern of rapid, age‐related changes in tactile processing toward lower discrimination thresholds (lower discrimination thresholds = greater sensitivity) across early childhood, though we acknowledge limitations with cross‐sectional data. Differences in the rate of change across tasks were observed, with tactile performance reaching adult‐like levels at a younger age on some tasks compared to others. Conclusions: While it is known that early childhood is a period of profound development including tactile processing, our data provides evidence for subtle differences in the developmental rate of the various underlying cortical, physical, and cognitive processes. Further, we are the first to show the feasibility of vibrotactile testing in early childhood (<6 years). The results of this work provide estimates of age‐related differences in performance, which could have important implications as a reference for investigating altered tactile processing in developmental disorders. Graphical Abstract: Tactile processing is essential in early child development and continues to develop throughout childhood and adolescence. Here, we examine the development of tactile performance across 5 tasks in 142 children and adults aged 3–23 years. All tasks show a pattern of rapid age‐related improvement that plateau by adulthood; however, there are pronounced differences in the rate of change. For example, we show a rapid decrease in reaction time (left) while simultaneous amplitude discrimination performance (right) develops more slowly.